2007
DOI: 10.1038/sj.mp.4001944
|View full text |Cite
|
Sign up to set email alerts
|

Physiogenomic comparison of weight profiles of olanzapine- and risperidone-treated patients

Abstract: Atypical antipsychotics induce pre-diabetic symptoms in some but not all patients, characterized most notably by elevated weight. The side effect profiles of the various drugs in the class differ, however, raising the possibility of drug-specific mechanisms for similar side effects. We used physiogenomic analysis, an approach previously employed to study the genetics of drug and diet response, to discover and compare genetic associations with weight profiles observed in patients treated with olanzapine and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 60 publications
2
43
0
Order By: Relevance
“…307 As the first marketed atypical antipsychotics are becoming off-patent and less expensive generic forms are available, it is also possible that pharmacogenetic testing for weight gain may become cost-effective. 308 In summary, the authors believed that future tests predicting antipsychotic response may need to include clinical and genetic variables to classify patients more accurately.…”
Section: Prediction Of Side Effectsmentioning
confidence: 99%
“…307 As the first marketed atypical antipsychotics are becoming off-patent and less expensive generic forms are available, it is also possible that pharmacogenetic testing for weight gain may become cost-effective. 308 In summary, the authors believed that future tests predicting antipsychotic response may need to include clinical and genetic variables to classify patients more accurately.…”
Section: Prediction Of Side Effectsmentioning
confidence: 99%
“…The association between AgRP, fat mass and appetite have been examined and were found to be disrupted in olanzapine-treated patients, but not in patients treated with ziprasidone [132]. Although an early study by Ruano and colleagues reported that a polymorphism (rs1468271) in the NPY gene had no association with body weight gain in patients treated with olanzapine and risperidone [133], a recent study by Tiwari and colleagues suggested a significant association between the SNPs rs16147, rs5573, and rs5574 in NPY and weight gain in clozapine and olanzapine-treated patients [134]. The same authors also revealed an association of rs6837793, near NPY 5 R, with the weight gain profile in patients treated with risperidone, which supported the role of the NPY system in SGAinduced weight gain.…”
Section: The Role Of Npy and Agrp In Sga-induced Weight Gainmentioning
confidence: 99%
“…A subsequent 9-month study in 75 neuroleptic-naïve Spanish schizophrenia patients found that the 2448A polymorphism did not predict short term weight gain (over 6 months), but was associated with 9 month weight gain (Templeman et al, 2005). Most recently, 29 single nucleotide polymorphisms (SNP) from 13 candidate genes were examined in a cross-sectional study of 67 olanzapine-and 101 risperidone-treated patients, including a SNP in the leptin receptor gene (rs8179183) associated with body weight in nonpsychiatric subjects (Ruano et al, 2007). Among this group of genetic markers, the leptin receptor SNP rs8179183 was found to have the strongest association with weight, and was significantly associated with weight profiles for the risperidone cohort (p<.001).…”
Section: Genetic Studiesmentioning
confidence: 99%